Evaluating Variability in Reflective Photoelasticity: Focus on Adhesives, Light Sources, and Camera Setup - Seongmin Kim; Boo-Hyun Nam; Young-Hoon Jung (Applied Sciences, 2023)
This study investigates the impact of various experimental parameters on the reflective photoelastic coating technique used to measure the stress and strain in model soil particles. The focus is directed towards three pivotal parameters: the choice of adhesive for the photoelastic coating, the inherent properties of the light source, and the configuration of the camera for color image analysis. Through a series of uniaxial compression tests on consistently crafted model soil particles, a notable relationship emerges between the adhesive’s shear strength, its viscosity, and the uniformity of the photoelastic response. While the light source’s characteristics and camera adjustments hold significance, their influence on the consistency of the response is comparatively subtle. Consequently, the adhesive’s role is underscored as instrumental in influencing the photoelastic response, offering valuable insights for subsequent research endeavors utilizing the reflective photoelastic technique.